The Impact of the CHILE Intervention on the Food Served in Head Start Centers in Rural New Mexico. (June 2016) - Morshed, Alexandra B.; Davis, Sally M.; Keane, Patricia C.; Myers, Orrin B.; Mishra, Shiraz I.
ABSTRACT: BACKGROUND: The Child Health Initiative for Lifelong Eating and Exercise is a multicomponent obesity‐prevention intervention, which was evaluated among Head Start (HS) centers in American Indian and predominantly Hispanic communities in rural New Mexico. This study examines the intervention's foodservice outcomes: fruits, vegetables, whole grains, discretionary fats, added sugars, and fat from milk served in meals and snacks. METHODS: Sixteen HS centers were randomized to intervention/comparison groups, following stratification by ethnicity and preintervention median body mass index of enrolled children. The foodservice component included quarterly trainings for foodservice staff about food purchasing and preparation. Foods served were evaluated before and after the 2‐year intervention, in the fall 2008 and spring 2010. RESULTS: The intervention significantly decreased fat provided through milk and had no significant effect on fruit, vegetables and whole‐grain servings, discretionary fats, and added sugar served in HS meals and snacks. When effect modification by site ethnicity was examined, the effect on fat provided through milk was only found in American Indian sites. CONCLUSIONS: Foodservice interventions can reduce the amount of fat provided through milk served in HS. More research is needed regarding the implementation of foodservice interventions to improve the composition of foods served in early education settings.